Exploring the Effects of Different Bacteria Additives on Fermentation Quality, Microbial Community and In Vitro Gas Production of Forage Oat Silage - Xiong, Yi; Xu, Jingjing; Guo, Linna; Chen, Fei; Jiang, Dedai; Lin, Yanli; Guo, Chunze; Li, Xiaomei; Chen, Yunrong; Ni, Kuikui; Yang, Fuyu (Animals (Basel), 2022)
Bacterial inoculants are considered as a good choice for successful ensiling, playing a key role in improving the silage quality. However, the potential of different bacteria, especially the propionic acid bacteria, in forage oat ensiling is yet to be explored. Therefore, the purpose of this study was to investigate the regulation effects of different bacterial additives on the fermentation quality of forage oat silage. Four additives (Lactiplantibacillus plantarum F1, LP; Lacticaseibacillus 0rhamnosus XJJ01, LR; Lacticaseibacillus paracasei XJJ02, LC; and Propionibacterium acidipropionici 1.1161, PP; without additives, CK) were inoculated in forage oat silage, and the fermentation quality and organic compounds were determined after 60 days of ensiling. Notably, LR showed higher dry matter preservation compared to other additives and CK. In addition, LP and LR showed strong lactic acid synthesis capacity, resulting in lower pH compared to other additives and CK. The treatments of PP and LC increased the bacterial diversity in silage, while the bacterial community in the LR group was different from that in other groups. In addition, the PP- and LC-treated oat silage showed significantly lower total in vitro gas production and a lower methane content. These results suggest that LP is more favorable for producing high-quality oat silage than LR, LC, or PP. Both the PP- and LC- treated oat silage may reduce rumen greenhouse gas emissions.